101 Pat-Downs : An Undercover Look at Airport Security and the TSA - Redden, Shawna Malvini (Book collections on Project MUSE., 2021)
"101 Pat-Downs traces the history of airport security since September 11, 2001, introducing assorted "characters" of airport security, from passengers who check their brains with their baggage to TSA agents who break the stereotypes"--